Noncoding RNAs evolutionarily extend animal lifespan - Anyou Wang (Global Medical Genetics)
The mechanisms underlying the evolution of lifespan across organisms remain mysterious. This study computes multiple large datasets and reveals that noncoding RNAs (ncRNAs), rather than proteins, drive animal lifespan evolution. Species in the animal kingdom evolutionarily increase their ncRNA length in their genomes, coinciding with trimming of the mitochondrial genome length. This leads to a low energy consumption and longevity. Notably, as species evolve and extend their lifespans, they tend to acquire long-lived ncRNA motifs while simultaneously losing short-lived ones, in contrast to the conservative patterns observed in protein evolution. These longevity-associated ncRNA motifs, such as GGTGCG, are particularly active in crucial tissues including the endometrium, ovaries, testes, and cerebral cortex. The ovary and endometrium carry more activating ncRNAs than the testis, offering insight into why women generally outlive men. Taken together, ncRNAs drive the evolution of the two most important traits of organisms: longevity and reproduction, and they execute many more fundamental functions than those conventionally thought. This discovery provides the foundation for combating longevity and aging.